2020
DOI: 10.3390/antiox9090873
|View full text |Cite
|
Sign up to set email alerts
|

Withanolide C Inhibits Proliferation of Breast Cancer Cells via Oxidative Stress-Mediated Apoptosis and DNA Damage

Abstract: Some withanolides, particularly the family of steroidal lactones, show anticancer effects, but this is rarely reported for withanolide C (WHC)—especially anti-breast cancer effects. The subject of this study is to evaluate the ability of WHC to regulate the proliferation of breast cancer cells, using both time and concentration in treatment with WHC. In terms of ATP depletion, WHC induced more antiproliferation to three breast cancer cell lines, SKBR3, MCF7, and MDA-MB-231, than to normal breast M10 cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…To provide a comparison with the clinically used anticancer drug cisplatin, the IC 50 value for cisplatin at 24 h in the MTS assay for SKBR3 cells was 49.8 μM [ 34 ]. The IC 50 concentrations for 48 h cisplatin in the ATP assay were 4.9, 17.9, and 26.9 μM for SKBR3, MCF7, and MDA-MB-231 cells, respectively [ 35 ]. For comparison, the IC 50 concentrations for 24 h PHA in the ATP assay were 4.18, 3.12, and 6.15 μM for SKBR3, MCF7, and MDA-MB-231 cells, respectively ( Figure 1 A).…”
Section: Discussionmentioning
confidence: 99%
“…To provide a comparison with the clinically used anticancer drug cisplatin, the IC 50 value for cisplatin at 24 h in the MTS assay for SKBR3 cells was 49.8 μM [ 34 ]. The IC 50 concentrations for 48 h cisplatin in the ATP assay were 4.9, 17.9, and 26.9 μM for SKBR3, MCF7, and MDA-MB-231 cells, respectively [ 35 ]. For comparison, the IC 50 concentrations for 24 h PHA in the ATP assay were 4.18, 3.12, and 6.15 μM for SKBR3, MCF7, and MDA-MB-231 cells, respectively ( Figure 1 A).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cell cycle disturbance may lead to apoptosis. For example, ginsenoside Rf [ 35 ], sinularin [ 36 ], curcumin [ 37 ], and withanolide C [ 38 ] induce G2/M arrest, which is frequently associated with apoptosis in cancer cells. Similarly, a combined treatment with UVC/CPC induces higher G2/M arrest than individual treatments (UVC or CPC) in oral cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that excessive production of ROS by exogenous means is more harmful to cancer cells ( 22 ). For instance, increasing ROS by exogenous drugs can cause apoptosis, DNA damage, or mitochondrial dysfunction of several cancers, including colorectal cancer, oral cancers, and breast cancer cells ( 44 46 ). We found that the effect of CVBD in inducing GBM cell apoptosis is related to the increase of intracellular ROS.…”
Section: Discussionmentioning
confidence: 99%